Effect of Proton Pump Inhibitor on Quality of Life in Patients having Laryngopharyngeal Reflux Disease - Sharma, S.; Pokhrel, M.; Kandel, S. (Devdaha Medical Journal, 2023)
Introduction: Laryngopharyngeal reflux is defined as the reflux of gastric content into the larynx and pharynx with symptoms like foreign body sensation in the throat, cough, heartburn, difficulty in swallowing, and hoarseness. Objective of this study was to find the effect of proton pump inhibitor on quality of life in patients having laryngopharyngeal reflux disease. Method: A Prospective study was conducted in Department of Ear Nose Throat (ENT) at Devdaha Medical College, Butwal between March 2023 to May 2023. Patients with suspected laryngopharyngeal reflux were evaluated using Reflux Symptom Index (RSI) and Reflux Finding Score (RFS) and treated with proton pump inhibitors (PPIs). Pre and post therapeutic RSI and RFS were compared. Result: A total of 75 patients were included over a period of 3 months. Mean total score of RSI and RFS before therapy was 1.51±2.102 and 0.99±1.297 and after therapy RSI and RFS was 0.87±1.383 and 0.44±0.773 (p<0.005) respectively. Conclusion: RFS and RSI are convenient and helpful in diagnosing LPR. Its use may prevent the unnecessary costs of invasive laboratory studies and imaging and time consuming examinations.